A bioactive polymethylmethacrylate bone cement for prosthesis fixation in osteoporotic hip replacement surgery. (1st November 2021) - Zheng, Zhibo; Chen, Siyu; Liu, Xudong; Wang, Yingjie; Bian, Yanyan; Feng, Bin; Zhao, Rui; Qiu, Zhiye; Sun, Yulong; Zhang, Hongyu; Cui, Fuzhai; Yang, Xiao; et al.
Graphical abstract: Highlights: PMMA-MC was fabricated as a biomaterial used in osteoporotic hip replacement surgery. PMMA-MC promoted the differentiation of osteoporotic MSCs towards osteoblasts. PMMA-MC improved implant osteointegration in an osteoporotic rat bone defect model.Application of PMMA-MC in elder cadaveric hip replacement is technically feasible. Application of PMMA-MC in elder cadaveric hip replacement is technically feasible. Abstract: Bioinert polymethylmethacrylate (PMMA) bone cement is the most conventional approach for quick fixation of the orthopedic implant during hip replacement surgery. However, problems with implant loosening occur frequently and particularly under osteoporosis due to inadequate osteointegration between the cement and host bone. In order to enhance osteointegration ability of the PMMA cement, mineralized collagen (MC) was incorporated into the PMMA (PMMA-MC) in the current study. An improved wettability and dynamic mechanical performance of the PMMA-MC was demonstrated in vitro, compared to pure PMMA. Then, the effect of PMMA and PMMA-MC on osteoporotic bone marrow stromal cells were investigated. The results revealed that the addition of MC could significantly up-regulate osteoblastic gene expressions (Runx2, Osx, and Alp) and down-regulate the expressions of adipogenic markers (C/EBPα, PPARγ-2, and adiponectin). The osteointegration ability of bone cement was evaluated in an osteoporotic rat model with bone defect. After 8 and 12 weeks of implantation, PMMA-MC group had significantly more new bone formation around the implant and a higher push-out force at the bone-cement surface than that of the PMMA group. Moreover, to simulate clinical hip replacement, prosthesis was fixed with either PMMA or PMMA-MC bone cement in osteoporotic cadaveric femurs. Compared to the PMMA group, more torque was required in the PMMA-MC group to achieve the same rotation degree in torsion test. These findings revealed the potential of MC to induce an efficient fixation between the modified cement surface and osteoporotic host bone. PMMA-MC can be a promising candidate biomaterial for clinical hip replacement.